PERANCANGAN INTERIOR ISLAMIC HEALTH AND SPORTS DENGAN TEMA SEMANGGI DI KOTA SURABAYA - Kenia Amalukha Riduwan; Ahmad Fadjar Ariyanto (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2019)
ABSTRACTInterior Design of Islamic Health and Sports in Surabaya City is an Islamic health and sports service building by applying the Semanggi theme. This design aims to produce interior design that can meet all the needs of Islamic health fulfillment activities comfortably and safely. The design method uses the design of Pamudji Suptandar, namely through the process of design input, synthesis, and output. The design approach uses the function, aesthetic, ergonomics, and sharia approach. The semanggi motif is taken from the transformation from pillars of the Rahmat Mosque in Surabaya by means of a contemporary style approach. This design has facilities including: Lobby, health & sports corner, pharmacy, examination room, therapy, trainer room, fitness room, Mixed Martial Arts area, retail, cafe, and lavatory which have separate zones between men and women in high privacy spaces .Key words :Interior, Islamic, Health, Sports, Semanggi ABSTRAK Perancangan Interior Islamic Health and Sports di Kota Surabaya merupakan bangunan pelayanan kesehatan dan rekreasi islami dengan menerapkan tema Semanggi. Perancangan ini bertujuan menghasilkan desain interior yang dapat memenuhi seluruh kebutuhan aktivitas pemenuhan kesehatan islami dengan nyaman dan aman. Metode perancangan menggunakan perancangan Pamudji Suptandar yaitu melalui proses desain input, sintesa, dan output. Landasan perancangan menggunakan pendekatan fungsi, estetika, ergonomi, dan syariah. Motif semanggi diambil dari transformasi daun semanggi pilar Masjid Rahmat Surabaya melalui pendekatan gaya kontemporer. Perancangan ini memiliki fasilitas diantaranya: Lobby, health & sports corner, apotek, ruang periksa, terapi, trainer, fitness, Mixed Martial Arts, retail, kafe, dan lavastory yang memiliki zona terpisah antara laki-laki dan perempuan pada ruang dengan tingkat privasi tinggi. Kata kunci : Interior, Islamic, Health, Sports, Semanggi.